Effectiveness, protection and composition of vaccines in the national vaccination calendar (Research, Society and Development, 2022)
Introduction: Vaccination is one of the most preventive means of disease transmission. These are created through the inclusion of pathogens such as bacteria, viruses or toxins. Once installed in the human body, vaccines stimulate the immune system reaction and the production of specific antibodies against the pathogenic agent. It is a fact that it cures diseases and prevents thousands more. In Brazil, vaccines are largely delivered to the population through the Unified Health System (SUS), undergoing a very detailed quality control, based on the precepts of the National Institute for Quality Control in Health (INCQS ). Objective: The objective of this work is to describe the efficacy, protection and composition of vaccines in the national vaccination schedule. Materials and methods: An integrative literature review was carried out, where the results of the main studies contained in the scientific databases SciELO, LILACS and PubMed in Portuguese and English were collected. RESULTS AND DISCUSSION: 11 articles that met the objectives and inclusion criteria were selected. A table was prepared with the purpose of objectively presenting the main information collected. Final considerations: In order to guarantee the effectiveness of the vaccines, their production undergoes strict quality control, and if it does not obtain adequate management in terms of storage, transport and handling, it will not have sufficient effects for users.